Guns for hire and enduring machines: clientelism beyond parties in Indonesia and the Philippines. Issue 1 (2nd January 2020) - Aspinall, Edward; Hicken, Allen
ABSTRACT: Since their transitions to democracy, electoral politics in Indonesia and the Philippines have become heavily clientelistic, marked by high levels of vote-buying and other forms of material exchange. In both cases, the organizational form taken by clientelism is similar: political candidates build informal pyramidal structures of brokers to connect them to voters, largely operating outside national parties. In the Philippines, these structures are local machines; in Indonesia, they are ephemeral organizations known as "success teams." Yet this similarity in form masks a deeper dissimilarity: in the Philippines, machines are built on a relational clientelism in which politicians cultivate brokers for the long-term; in Indonesia, the modal pattern is short-term transactional relationships. We demonstrate this distinction by drawing on fieldwork and broker surveys conducted in both countries, and attribute it to a combination of historical legacies and electoral rules. In particular, differences in electoral institutions shape the incentives and capacities of politicians to invest in lasting machines, encouraging coordination among candidates when building campaign structures and sharing resources in the Philippines; impeding such cooperation in Indonesia. Our analysis suggests that scholars of patronage politics need to look beyond parties and to consider differences between relational and transactional varieties of clientelism.